2017
DOI: 10.1177/1076029617693939
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Relevance of ASA Nonresponse After Cardiac Surgery: A Prospective Bicentric Study

Abstract: We aimed to identify the prevalence of acetylsalicylic acid (ASA) nonresponse in patients after coronary artery bypass graft (CABG) surgery and the possible consequences for the rate of major cardiovascular events. This prospective, observational, bicentric cohort study was conducted in two German University hospitals. A total of 400 patients (200 in each study center) undergoing elective CABG surgery were enrolled after written informed consent. Platelet function was analyzed on day 3 (d3) and day 5 (d5) post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…In contrast to Wand et al 14 we did not find a significant positive correlation between the surgical procedure time and nonresponder rate (p = 0.65). While the highest number of nonresponders was found in the EVAR group with the longest procedure time, the differences between the groups were not significant.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to Wand et al 14 we did not find a significant positive correlation between the surgical procedure time and nonresponder rate (p = 0.65). While the highest number of nonresponders was found in the EVAR group with the longest procedure time, the differences between the groups were not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…The postoperative analgesia regimen in our trial mainly included NSAIDs and the pyrazolinone metamizole, which may have a supplement effect to the ASA nonresponder rate because of potential medical interference as they both practice their effect via the cyclooxygenase. 14 Last but not least, the omnipresent problem of noncompliance is the most usual cause for ASA nonresponse. 24,25 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It measures platelet aggregation by continuously monitoring electrical impedance changes due to activation of platelets and adhesion to the metal sensor electrodes in 3-5 separate channels in multiple electrode aggregometry (MEA). [14][15][16][17][18][19][20][21] Whole blood sample is used in each channel with the addition of arachidonic acid to assess the effect of aspirin (ASPItest ), ADP for platelet P2Y12 inhibitor effect (ADPtest ) or thrombin receptor agonist peptide to measure glycoprotein IIb/IIIa inhibitor effect (TRAPtest ). 14,[19][20][21] Collagen can also be used as a substitute for arachidonic acid to assess the effect of aspirin.…”
Section: Impedance Platelet Aggregometrymentioning
confidence: 99%
“…A study on 60 patients who went to elective OPCABG and were divided into two groups to receive mono-antiplatelet treatment (MAPT) with ASA or DAPT with ASA and clopidogrel has shown that clopidogrel in addition to ASA reduces the incidence of OPCABGrelated aspirin resistance, DAPT can be safely applied early after surgery, and there were no significant differences between two groups in postoperative bleeding [49]. A recent prospective, observational, bicentric cohort study indicated a high incidence of perioperative ASA nonresponse in patients following CABG, and no effect on the incidence of cardiovascular events was recorded in the 1-year follow-up [50]. Similar was concluded in a small low-risk cohort patients in which reduced ASA responsiveness as assessed with impedance aggregometry was not associated with increased incidence of major adverse cardiac and thromboembolic events and mortality after CABG surgery [51].…”
Section: Resistance To Antiplatelet Therapy and Its Clinical Significmentioning
confidence: 99%